‘Filming Is Our Only Weapon Against the Police’: ethnic Minorities and Police Encounters in the New Visibility Era - Søgaard, Thomas Friis (The British journal of criminology, 2023)
Based on Goldsmith’s (2010, ‘Policing’s New Visibility’, British Journal of Criminology, 50: 914-34) assertion that police work has acquired a ‘new visibility’ with the ubiquity of cell phone cameras, recent studies have explored how ‘video activists’ often film the police as means of protecting marginalised ethno-racial communities. However, limited research exists on how non-activist ethno-racial minority young people use cell phone cameras in encounters with the police. Based on 37 interviews conducted in Denmark, this paper explores the multifaceted nature of marginalised ethnic minority young people’s use of cell phone cameras in police encounters. We demonstrate how the filming of officers is interwoven with the young people’s street culture, and how the use of cameras holds the potential to counter traditional power imbalances, while nevertheless, potentially exacerbating their antagonism towards the police.